The Bibliometric Analysis of a Bibliography of the Works on the Prophet Muhammad in Western Languages - Rauf Ahmed; Dr. Muhammad Islam (MEI, 2022)
This paper presents a bibliometric analysis of “The Prophet Muhammad (peace be upon him): A Select Bibliography in Western Languages,” published in 2015 by Islamic Research Institute, International Islamic University, Islamabad, Pakistan on sirah (a genre of literature that discusses the life of the Prophet Muhammad). The sirah has a rich scholarly tradition with a long history. The analysis identifies different trends in books, journal articles, book chapters, encyclopedic articles, conference papers, and theses/dissertations included in the above bibliography. MS Excel and Open Refine have been used for data collection and refinement. The article shows that the books made the major part of the bibliography. Thirty per cent of books in the bibliography were published in Pakistan. Indian Muslim scholar Sayyid Abu al-Hasan Ali Nadvi was the most prolific author in terms of the number of publications. The dominant topic was the general life of the Prophet. Last but not least, the “Muslim World” journal ranked first in the bibliography in terms of producing articles on the life of the Prophet. The article will help the scholars identify major trends in the works on the Prophet Muhammad in Western languages.